Strategi geopolitik Indonesia dalam menjaga stabilitas nasional di tengah persaingan global - Abdurrahman, Nauval (Maliki Interdisciplinary Journal, 2026)
The changing condition of international affairs has increased global competition in many sectors, including politics, economy, defense, technology, and control over strategic regions. This situation places Indonesia in an important position because the country lies on international trade routes and is part of the Indo-Pacific area that has become a major focus of world powers. This study aims to examine Indonesia’s geopolitical strategy in maintaining national stability amid increasingly complex global rivalry. The research applies a qualitative method through library research by using various references such as academic journals, books, news sources, and official documents related to Indonesian geopolitics and geostrategy. The findings indicate that Indonesia carries out several strategic efforts through the strengthening of its free and active foreign policy, expanding cooperation within ASEAN, improving national economic resilience, reinforcing maritime security, and optimizing national resources to support state stability. In addition, Indonesia attempts to maintain balanced relations with major countries in order to avoid pressure and conflicts of international interests. These strategies are implemented to protect national security, preserve state sovereignty, and strengthen Indonesia’s role in global relations. In conclusion, Indonesia’s geopolitical strategy has an important function in responding to global dynamics while maintaining national stability in the midst of rapid international changes.